1958
DOI: 10.1104/pp.33.1.70
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Triiodobenzoic Acid and Maleic Hydrazide upon the Transport of Foliar Applied Calcium and Iron.

Abstract: ham University (Newcastle Division, King's College) 1957. 25. KORNBERG, H. and KREBS, H. A. Synthesis of cell constituents from C-units by a modified tricarboxylic acid cycle. Nature 179: 988-991. 1957. 26. BRADBEER, J. W. Some carbohydrate and acid conversions in Kalanchoe crenata. Ph.D. Thesis, Durham University (Newcastle Di-ision, King's College) 1954. 27. STILLER, M. Experiments on the relationship between succulence and acid accumulation in Bryophyllum, with an addendum on the mechanism of acid accumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1959
1959
2011
2011

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…These could enhance the absorption by the leaf at the site of application, increase the migration within the leaf, and/or stimulate the transport out of the leaf in the acropetal or basipetal direction. Kessler and Moscicki (1958) reported that TIBA (triiodobenzoic acid) and MH (maleic hydrazide) increased the downward transport of 45 Ca supplied to the apple leaves. Application of GA 3 or CCC (chloroethyl choline chloride) and kinetin influenced foliar uptake of Fe, and kinetin increased its translocation (Kannan and Mathew, 1970).…”
Section: B Influence Of Growth Regulatorsmentioning
confidence: 98%
“…These could enhance the absorption by the leaf at the site of application, increase the migration within the leaf, and/or stimulate the transport out of the leaf in the acropetal or basipetal direction. Kessler and Moscicki (1958) reported that TIBA (triiodobenzoic acid) and MH (maleic hydrazide) increased the downward transport of 45 Ca supplied to the apple leaves. Application of GA 3 or CCC (chloroethyl choline chloride) and kinetin influenced foliar uptake of Fe, and kinetin increased its translocation (Kannan and Mathew, 1970).…”
Section: B Influence Of Growth Regulatorsmentioning
confidence: 98%
“…Thus translocation was obtained by dehydrating the plants (Biddulph, Cory, and Biddulph 1959;Taylor, Moore, and Drinkwater 1961), by treatment with diethyl ether (Bukovac, Wittwer, and Tukey 1956;Biddulph, Cory, and Biddulph 1959), and in some instances by treatment with 2,3,5-triiodobenzoic acid (Kessler and Moscicki 1958;Bukovac and Wittwer 1961). Taylor, Moore, and Drinkwater (1961) were unsuccessful when they used the latter compound as a translocating agent.…”
Section: Introductionmentioning
confidence: 99%
“…Growth substances are known to increase, retard, or modify plant growth by affecting diverse metabolic processes (18,19), and it is likely that these substances also affect the mechanism of ion uptake (17). However, very little information relating to the action of growth substances on the absorption and transport of Fe is available in the literature (1,12,20). The present paper deals with the effects of 6-furfurylaminopurine, gibberellic acid, 2-chloroethyltrimethylammonium chloride, N,N-dimethylaminosuccinamic acid, 4-hydroxy-5-isopropyl-2-methylphenyl trimethylammonium chloride 1-piperidine carboxylate (Amo 1618), and triiodobenzoic acid on Fe absorption by leaves and roots, and its transport to other organs.…”
mentioning
confidence: 99%